(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we propose several solar cell designs based on metamaterials. Extensive numerical simulations of various designs with different materials are carried out. Our tests show that metamaterial solar cells are quite efficient, and over 80% and 90% absorption rates can be attained for solar spectrum and visible rays, respectively.